HOME INDUSTRY AS A MICRO-BUSINESS EMPOWERMENT STRATEGY IN INCREASING WORKERS' FINANCIAL REVENUE (CASE STUDY OF MAMA ZITA'S CAKE HOME INDUSTRY IN BANTAN VILLAGE) - Elva Damayanti; Evalina Pakpahan; Nela Permata Sari Lubis; Daniel Ebenezer Silaban (Yayasan Amanah Nur Aman, 2026)
This study examines the role of home industry as a strategy for empowering micro-businesses in increasing workers' financial revenue, with a case study of the Mama Zita cake home industry in Bantan Village. The research problem arises from several issues, including the lack of skill empowerment programs for workers from government institutions, limited marketing strategies in promoting products, and minimal attention to raw material management, production facilities, and access to capital that support business sustainability. This study aims to analyze how the home industry contributes to empowering micro-entrepreneurs and improving workers’ financial income. The research uses a qualitative approach in which the researcher acts as the key instrument. Data were collected through triangulation techniques including interviews, observations, photographs, and documentation, while data analysis was conducted inductively to interpret meanings rather than generalize findings. The results show that the Mama Zita cake home industry plays a strategic role in community economic empowerment. As a household-based business with flexible operations and relatively small capital requirements, the home industry provides employment opportunities, supports micro-entrepreneurs, and contributes to strengthening household economic resilience. Furthermore, workers involved in this sector experience a significant increase in daily financial income and receive additional bonuses when production orders increase. Therefore, the home industry can be considered an effective alternative strategy for empowering micro-businesses and improving workers’ financial welfare at the community level.